Giant landslide triggerings and paleoprecipitations in the CentralWestern Andes: The aricota rockslide dam (South Peru) - Delgado Madera, Gabino Fabrizio (2019)
The central part of the Western Andes holds an exceptional concentration of giant paleolandslides involving very large volumes of rock material (v > km3). While those gravitational slope failures are interpreted consensually as an erosional response to the geodynamic activity of the Andes (relief formation and tectonic activity), the question of their triggering mechanisms remains enigmatic. To clarify the respectiveroles of climatic versus seismic forcing on the Andean landslides, new temporal constraints on paleomovements are essential. Here, we focus on one of those giant slope failures, the Aricota giant rockslide that damned the Locumba valley in southern Peru. We conducted fieldwork, high-resolution DEM analysis and cosmogenic nuclide dating to decipher its development history and failure mechanisms. Our results point to the occurrence of two successive events. A giant failure mobilizing a rock volume of ca.2 km3 first produced a dam at 17.9 ± 0.7 ka. Considering its height of ca. 600 m, the Aricota rockslide dam is one of the three largest landslide dams worldwide. At 12.1 ± 0.2 ka, a second event produced ca. 0.2km3 of material, and the rock-avalanche debris spread out over the dam. As the chronology of those two events is pointing to the two main paleoclimatic pluvial periods in this region (Heinrich Stadial 1a and Younger Dryas), we favor the interpretation of a climatic forcing. At a regional scale, the concomitant aggradation of alluvial terraces and fan systems along the nearby valleys highlights higher regional erosion, sediments supply and mass-wasting events during those paleoprecipitation events and strengthens this conclusion.